Myelinating Proteins in MS Are Linked to Volumetric Brain MRI Changes. Issue 3 (12th February 2019) - Brod, Staley A.; Lincoln, John A.; Nelson, Flavia
ABSTRACT: BACKGROUND AND PURPOSE: There is evidence of a relationship between promyelinating proteins and clinical multiple sclerosis (MS) activity during clinical relapse or recovery from clinical relapses. We examined the linkage between promyelinating biomarkers and volumetric changes in MS subjects during serial magnetic resonance imaging (MRI). METHODS: We enrolled 13 MS subjects with active brain MRI scans not on disease modifying therapies. Subjects underwent baseline MRI, serum, and cerebrospinal fluid (CSF) sampling. Qualitative changes, new/resolving gadolinium, new/enlarging/diminishing T2 and T1 hypointense lesions, were compared to baseline in subsequent MRI scans, and volumetric analysis was calculated. Analysis of biomarkers on serial CSF samples was performed only in subjects with qualitative (and quantitative) changes on MRI. The study was performed at a MS Center of Excellence academic medical center. RESULTS: There was increased CSF neural cell adhesion molecule (N‐CAM) during increased qualitative T1 activity. A positive correlation between CSF and serum N‐CAM and T1 lesion volume was observed. A negative correlation between serum brain‐derived neurotrophic factor (BDNF) and BPH (T1 vol/T2 vol + T1 vol) was observed. CONCLUSIONS: Increased N‐CAM levels may be related to repair or remyelination following injury to the brain as shown by increased T1 volumes. Our data suggest an early kind of blood signaling that induces release of peripheral BDNF levels.